1996
DOI: 10.1096/fasebj.10.7.8635694
|View full text |Cite
|
Sign up to set email alerts
|

Expression and release of LAG‐3‐encoded protein by human CD4 + T cells are associated with IFN‐γ production

Abstract: The lymphocyte activation gene (LAG) -3 is a member of the immunoglobulin super-family that is selectively transcribed in human activated T and NK cells. In this work, the possibility that LAG-3 expression by human CD4+ T cells was preferentially related to one or another phenotype of cytokine secretion was investigated. Surface LAG-3 expression correlated with IFN-gamma, but not IL-4, production in antigen-stimulated T cells and it was up-regulated by IL-12. Most activated CD4+ T cell clones with established … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 104 publications
(77 citation statements)
references
References 16 publications
6
71
0
Order By: Relevance
“…Our observation that normal resting C57BL/6 mice had sLAG-3 in their serum was consistent with previous studies in humans (2,17,18,24). However, these previous studies have suggested that human sLAG-3 is produced by alternative splicing, although no detailed molecular or biochemical evidence has been provided.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our observation that normal resting C57BL/6 mice had sLAG-3 in their serum was consistent with previous studies in humans (2,17,18,24). However, these previous studies have suggested that human sLAG-3 is produced by alternative splicing, although no detailed molecular or biochemical evidence has been provided.…”
Section: Discussionsupporting
confidence: 93%
“…LAG-3 is expressed as a type I transmembrane protein on the cell surface (7). Interestingly, a soluble form of LAG-3 (sLAG-3) was detected by ELISA in human serum (17). In a recent study it was shown that serum samples from active tuberculosis patients had lower soluble LAG-3 level than those from uninfected individuals (18).…”
Section: Biochemical Analysis Of the Regulatory T Cell Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…The Th1-associated molecules include CD26 [4], membrane IFN-␥ [5], and lymphocyte activation gene (LAG)-3 [6], whereas CD62L [7] and CD30 [8] have been shown to be preferentially expressed by Th2 cells. More recently, it has been reported that some chemokine receptors can also associate with human Th1 or Th2 cells, suggesting their possible role in favoring the selective attraction of the two Th cell subsets, as well as in regulating their migration in inflammatory sites.…”
Section: Introductionmentioning
confidence: 99%
“…5, A and B, upper panels). Because it has been previously reported that LAG-3 could be shed from the membrane by protease-specific mechanisms in mice (22) and could be secreted as a truncated soluble form through an alternative splicing event of the mRNA in humans (23,16), the release of a LAG-3 soluble form by these T cells was also investigated. Stimulation of T cell clone TB39 with peptide-loaded autologous lymphoblastoid cell line induced about a two-fold increase in the release of soluble LAG-3 if compared with stimulation with LCL alone (Fig.…”
Section: Lag-3 Expressed By Ag-specific and Activated T Cells Exerts mentioning
confidence: 99%